2015
DOI: 10.1002/chir.22442
|View full text |Cite
|
Sign up to set email alerts
|

EnantioselectivePhotolysis and Quantitative Chiral Analysis of Tryptophan Complexed With Alkali‐Metalized L‐Serine in the Gas Phase

Abstract: The enantioselective photolysis of a cold gas-phase noncovalent complex of tryptophan with alkali-metalized L-serine, M(+) (L-Ser)(Trp) (M = Na and Li), was examined using a tandem mass spectrometer containing a variable-temperature ion trap. CO2 loss from Trp in the clusters was enantiomerically selective in ultraviolet excitation with linearly polarized light. M(+) (L-Ser) promoted the enantioselective photolysis of Trp as a chiral auxiliary. The enantioselective photolysis of the D-enantiomer was applied to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Trp, Phe, Tyr, and His contain indole, benzene, phenol, and imidazole side chains, respectively. Ser was formed by the ultraviolet irradiation of interstellar ice analogs [ 19 , 20 ], and showed enantiomer-selectivity in the gas phase [ 31 , 37 , 38 ]. Based on the results, we determined the amino-acid sequences of tripeptides needed for the recognition of aromatic amino acids.…”
Section: Introductionmentioning
confidence: 99%
“…Trp, Phe, Tyr, and His contain indole, benzene, phenol, and imidazole side chains, respectively. Ser was formed by the ultraviolet irradiation of interstellar ice analogs [ 19 , 20 ], and showed enantiomer-selectivity in the gas phase [ 31 , 37 , 38 ]. Based on the results, we determined the amino-acid sequences of tripeptides needed for the recognition of aromatic amino acids.…”
Section: Introductionmentioning
confidence: 99%
“…[15] We have previously examined the UV photodissociation of cold gas-phase Trp enantiomers, both on a chiral crown ether and in L-serine clusters, as a model for interstellar molecular clouds. [16][17][18] This work indicated that enantioselective photodissociation of cold gas-phase amino acids on chiral substances by linearly polarized light could have played an important role in the origin of homochirality in biomolecules. This enantioselective photodissociation with linearly polarized light was applied to quantitative chiral analysis.…”
mentioning
confidence: 96%
“…The rate constants of two competitive dissociation pathways relate to the ion intensities of the product ions, and the natural logarithm plot was used for chiral recognition using mass spectrometry-based techniques. [8,9,11,18] A linear relationship for ln(R) versus the L-enantiomer fraction is obtained, with a slope of 1.867, an intercept of À1.078 and a correlation coefficient (r 2 ) of 0.989. This indicates that the optical purity of Trp can be determined by measuring the relative abundance ratio R in a photodissociation mass spectrum and by referring to the linear relationship shown in Fig.…”
mentioning
confidence: 99%